Assessment of human resources for health using cross-national comparison of facility surveys in six countries - Dal Poz Mario R; Gupta Neeru (Human Resources for Health, 2009)
Abstract Background Health facility assessments are being increasingly used to measure and monitor indicators of health workforce performance, but the global evidence base remains weak. Partly this is due to the wide variability in assessment methods and tools, hampering comparability across and within countries and over time. The World Health Organization coordinated a series of facility-based surveys using a common approach in six countries: Chad, Côte d'Ivoire, Jamaica, Mozambique, Sri Lanka and Zimbabwe. The objectives were twofold: to inform the development and monitoring of human resources for health (HRH) policy within the countries; and to test and validate the use of standardized facility-based human resources assessment tools across different contexts. Methods The survey methodology drew on harmonized questionnaires and guidelines for data collection and processing. In accordance with the survey's dual objectives, this paper presents both descriptive statistics on a number of policy-relevant indicators for monitoring and evaluation of HRH as well as a qualitative assessment of the usefulness of the data collection tool for comparative analyses. Results The findings revealed a large diversity in both the organization of health services delivery and, in particular, the distribution and activities of facility-based health workers across the sampled countries. At the same time, some commonalities were observed, including the importance of nursing and midwifery personnel in the skill mix and the greater tendency of physicians to engage in dual practice. While the use of standardized questionnaires offered the advantage of enhancing cross-national comparability of the results, some limitations were noted, especially in relation to the categories used for occupations and qualifications that did not necessarily conform to the country situation. Conclusion With increasing experience in health facility assessments for HRH monitoring comes greater need to establish and promote best practices regarding methods and tools for their implementation, as well as dissemination and use of the results for evidence-informed decision-making. The overall findings of multi-country facility-based survey should help countries and partners develop greater capacity to identify and measure indicators of HRH performance via this approach, and eventually contribute to better understanding of health workforce dynamics at the national and international levels.